Faire naître l’espoir et l’auto-efficacité chez les jeunes par l’action environnementale communautaire - Kerry, Jackie; Pruneau, Diane; Cousineau, Maryse; Mallet, Marie-Andrée; Laliberté, Brigitte; Langis, Joanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
Youth sometimes demonstrate attitudes that are unfavorable to their involvement in community environmental actions: despair and impression that it is difficult for them to change the situation. The goal of this research was to observe and measure primary school students’ hope and self-efficacy in regards to environmental action, while they experienced some pedagogical strategies that reinforce self-efficacy. The quantitative and qualitative results of this case study demonstrate fluctuations in students’ hope and self-efficacy at different times in the project. Those two attitudes also varied according to grade level and conceptions of environmental action. Recommendations are suggested to accompany students toward the accomplishment of environmental actions.